Artesunate inhibits the development of PVR by suppressing the TGF-β/Smad signaling pathway. (December 2021) - Wang, Zi-Yi; Zhang, Yu; Chen, Jie; Wu, Ling-Dan; Chen, Mei-Ling; Chen, Ci-Min; Xu, Qi-Hua
Abstract: Proliferative vitreoretinopathy (PVR) is the main cause of retinal detachment surgery failure. The epithelial-mesenchymal transition (EMT) induced by transforming growth factor (TGF-β2) plays an important role in the development of PVR. Artesunate has been widely studied as a treatment for ophthalmic diseases because of its antioxidant, anti-inflammatory, antiapoptotic and antiproliferative properties. The purpose of this study was to investigate the effects of artesunate on the TGF-β2-induced EMT in ARPE-19 cells and PVR development. We found that artesunate inhibited the proliferation and contraction of ARPE-19 cells after the EMT and the autocrine effects of TGF-β2 on ARPE-19 cells. Additionally, the levels of Smad3 and p-Smad3 were increased in clinical samples, and artesunate decreased the levels of Smad3 and p-Smad3 in ARPE-19 cells treated with TGF-β2. Artesunate also inhibited the occurrence and development of PVR in vivo. In summary, artesunate inhibits the occurrence and development of PVR by inhibiting the EMT in ARPE-19 cells. Highlights: A conformational activation of Smad signaling pathway in PVR disease. Artesunate can decreased the activation of TGF/Smad signaling pathway. Artesunate inhibits the epithelial-mesenchymal transition of ARPE-19 cells induced by TGF. Artesunate can inhibits PVR progression in vivo.